PWE-038 Influence of postoperative morbidity on longterm cancer survival after oesophagogastric surgery. (28th May 2012) - Eltweri, A; Satheesan, S; Ubhi, S; Bowrey, D
Abstract : Introduction: Previous studies have shown that postoperative adverse events after colorectal resection predict a poor prognosis with early cancer relapse. The aim of this study was to report the outcome of patients undergoing oesophagogastric resection to assess the influence of in-hospital factors on longterm cancer survival. Methods: Retrospective review of patients undergoing oesophagogastric resection for carcinoma during the years 2006–2010 at our institution. Minimum follow-up of 12 months was required. Results: The study population was 164 patients (110 male) of median age 64 years (range 32–84). 84 underwent oesophagectomy, 80 gastrectomy. 99 received neoadjuvant chemotherapy. The 90-day, 1-year and 3-year survivals were 92%, 84% and 49% respectively. 69 patients (42%) developed postoperative complications (commonest: pneumonia 19%, anastomotic leak 7%, wound infection 6%). None of tumour site (oesophagus vs stomach, p=0.73), length of ITU stay (<3 days vs >3 days, p=0.50) or development of postoperative complications (p=0.70) influenced longterm prognosis. The only two factors that influenced longterm outcome were UICC stage (p<0.001) and circumferential resection margin (positive vs negative, p<0.001). Conclusion: Patients experiencing postoperative morbidity can expect the same longterm oncologic outcome as those not suffering these early setbacks. Competing interests: None declared.